Association of Hypertriglyceridemia with All‐Cause Mortality and Atherosclerotic Cardiovascular Events in a Low‐Risk Italian Population: The TG‐REAL Retrospective Cohort Analysis - Marcello Arca; Chiara Veronesi; Laura D’Erasmo; Claudio Borghi; Furio Colivicchi; Gaetano Maria De Ferrari; Giovambattista Desideri; Roberto Pontremoli; Pier Luigi Temporelli; Valentina Perrone; Luca Degli Esposti (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2020)
Background Evidence regarding the relationships among high plasma triglycerides (TG), all‐cause mortality, and atherosclerotic cardiovascular disease (ASCVD) events in low‐to‐moderate risk individuals is limited. The aim of this study was to determine whether the presence of high TG levels influences the risk of all‐cause mortality and ASCVD events in a population cohort followed in the real‐world clinical setting. Methods and Results A retrospective longitudinal cohort analysis using administrative databases of 3 Italian Local Health Units was performed. All individuals with at least one TG measurement between January 1, 2010 and December 31, 2015 were followed through December 2016. Outcome measures included incident ASCVD events and all‐cause mortality. Individuals with normal TG levels (<150 mg/dL) were compared with those with high (150–500 mg/dL) and very high TG (>500 mg/dL). 158 042 individuals (142 289 with normal, 15 558 with high, and 195 with very high TG) were considered. In the whole cohort, the overall incidence rates of ASCVD and all‐cause mortality were 7.2 and 17.1 per 1000 person‐years, respectively. After multivariate adjustment for potential confounders, individuals with high and very high TG showed a significantly increased risk of all‐cause mortality (hazard ratio [HR]=1.49 [95% confidence interval (CI) 1.36–1.63], P<0.001, and HR=3.08 [95% CI 1.46–6.50], P<0.01, respectively) and incident ASCVD events (HR=1.61 [95% CI 1.43–1.82], P<0.001, and HR=2.30 [95% CI 1.02–5.18], P<0.05, respectively) as compared to those with normal TG. Conclusions Moderate‐to‐severe elevation of TG is associated with a significantly increased risk of all‐cause mortality and ASCVD events in a large cohort of low‐to‐moderate cardiovascular risk individuals in a real‐world clinical setting.